As modalidades oral e escrita e o uso dos modalizadores - Otoni, Maria Aparecida Resende (Cadernos de Linguagem e Sociedade, 2010)
This paper aims to analyze two written narratives: Chapter V and Chapter VI of the novel O falador, by Mário Vargas Llosa. In spite of being written, Chapter V is an oral story telling through writing and it has a lot of features identified as characterizing oral discourse. On the other hand, Chapter VI presents Llosa’s biography and it follows the conventions of written language. Based on Chafe’s view (1985) that the hedging of categorizations is restricted to spoken language, we analyze the occurrence of modals in the two chapters, attempting to verify that in Chapter V there is the same tendency pointed out by Chafe for spoken language.